Oral hygiene practices of non-dental nurses in a tertiary hospital in North-West Nigeria - Zainab F Ibrahim; Lawal O Teslim; Ibrahim Aliyu (Wolters Kluwer Medknow Publications, 2017)
Introduction: Poor oral hygiene results in dental caries and this has been associated with cardiovascular morbidities. Therefore achieving a good oral hygiene will significantly improve the quality of health. Materials and Methods: This was a crosssectional study; it was carried out between October and December 2016. Non-dental nurses in the hospital were consecutively recruited, and a pretested selfadministered questionnaire was administered. Results: There were 36 (37.1%) males, 61 (62.9%) females with male to female ratio of 1:1.7. Sixtysix percent of the respondents used toothbrush and paste for oral cleansing. However, majority of them changed their brush on 2-3 monthly basis; similarly, 56 (57.7%) of the respondents brushed at least twice in a day. Fortysix (47.4%) of the respondents used mouth wash while 51 (52.6%) did not; and among the nonusers, the majority (47.1%) believed mouth wash was ineffective. Thirtyeight (39.2%) of the respondents did brush for <4 min while 59 (60.8%) brushed for at least 4 min. Nine (14.3%) respondents used dental filament. Fifty (51.5%) of the respondents used mouthwash while 47 (48.5%) did not use mouthwash; however, among 46 respondents who did not use mouth wash, 24 (52.2%) believe that mouth wash are ineffective, 12 (26.1%) did not like mouthwash, 7 (15.2%) were unaware of mouth wash, 2 (4.3%) reported cost as a deterrent; whereas 1 (2.2%) said mouth wash was not available in their vicinity. Conclusion: Commendable oral hygiene practices were observed among the respondents; however, there is knowledge gap which requires improvement such as the use of dental floss.